Application of parallel algorithms for solving the problem of fluid flow to wells with complicated configurations in fractured porous reservoirs - Gubajdullin, D.A.; Sadovnikov, R.V. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2007)
The questions related to solving the problems of fluid flow to wells with different trajectories (vertical, inclined, horizontal, etc.) on high performance computers are considered. The finite element method is used on unstructured grids of tetrahedrons. The resulting system of linear algebraic equations is solved with the use of the Aztec parallel iterative library that includes a number of Krylov iterative methods with different preconditioners on the basis of the MPI-technology.